1684. Hospital Costs and Reimbursement in Patients with Resistant Enterobacteriaceae (ENT) Urinary Tract Infection (UTI) in the United States (US): A Multicenter Analysis. (31st December 2020) - Melnick, David; Jain, Akash; Gupta, Vikas; Sulham, Katherine
Abstract: Background: Rates of fluoroquinolone resistance (FQ-R) and third-generation cephalosporin resistance/extended-spectrum beta-lactamases (ESBL+) are rising. These pathogens generally retain susceptibility to intravenous (IV) carbapenems; however, the loss of susceptibility to commonly used oral (PO) antibiotics limits the opportunity to transition these patients home, leading to increased length of stay (LOS) and higher costs. Here, we evaluate the hospital LOS, costs and reimbursement for UTI hospitalizations. Methods: We analyzed the first positive enterobacteriaceae (ENT) urine culture ≤ 3 days from hospital admission in patients with a primary or secondary UTI ICD10 discharge diagnosis from 68 US hospitals admitted October 1, 2015-2017. Patient characteristics and outcomes were categorized by ESBL+ and FQ-R status. IV to PO was identified as PO therapy after 24 hours of IV. Outcomes were stratified by resistance and PO conversion status. Results: 16, 022 patients were eligible for analysis; 5, 017 (31.3%) were FQ-R, 1, 763 (11.0%) were ESBL+, and 1, 433 (8.9%) were both FQ-R and ESBL+; 2, 367 (14.8%) were converted to PO antibiotics during their hospitalization. Overall, mean LOS, costs, and reimbursement were 5.2 days, 9, 303 and 8, 501 (mean difference between cost and reimbursement: -878). Mean LOS was shorter and mean difference between cost and reimbursement was lower overall for patients converted to PO therapy vs. those who did not (4.7 vs. 5.3 days, -532 vs. -938). Drug resistance was associated with higher LOS and a larger difference between cost and reimbursement; patients who were FQ-R and ESBL+ and did not convert to PO had a mean LOS of 6.0 days, costs of 11, 482, and reimbursement of 9, 243 (difference: -2, 446). Mean LOS, costs, and reimbursement for patients who were neither FQ-R nor ESBL+ and who did convert to PO therapy were 4.6 days, 7, 904, and 7, 496 (difference: -527), respectively. Conclusion: Reduced LOS and substantial cost savings could be recognized by efficiently converting patients receiving IV antimicrobials to PO and discharging them from the hospital. Lack of PO therapies with activity against resistant pathogens has made this challenging; new PO options may help reduce hospital costs and resources required to treat these UTI patients. Disclosures: David Melnick, MD, Spero Therapeutics (Employee)Spero Therapeutics (Employee) Akash Jain, PhD, Spero Therapeutics (Employee) Vikas Gupta, PharmD, BCPS, Becton, Dickinson and Company (Employee, Shareholder)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Katherine Sulham, MPH, Spero Therapeutics (Independent Contractor)